2014
DOI: 10.1002/j.0022-0337.2014.78.3.tb05686.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Critical Thinking and Evidence–Based Dentistry Across a Four–Year Dental Curriculum: A Model for Independent Learning

Abstract: Introducing critical thinking and evidence-based dentistry (EBD) content into an established dental curriculum can be a dificult and challenging process. Over the past three years, the University of Iowa College of Dentistry has developed and implemented a progressive four-year integrated critical thinking and EBD curriculum. The objective of this article is to describe the development and implementation process to make it available as a model for other dental schools contemplating introduction of critical thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 8 publications
1
41
0
1
Order By: Relevance
“…For the success of the pilot course, it is important that TUSDM ensures that critical thinking, communication, teamwork, and skills in clinical and behavioral sciences remain at a high standard and be periodically revised to meet the needs of both students and faculty. This is different than in a study conducted at the University of Iowa, which focused on EBD implementation for all four years but was separated by class requirements and classes 21 …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…For the success of the pilot course, it is important that TUSDM ensures that critical thinking, communication, teamwork, and skills in clinical and behavioral sciences remain at a high standard and be periodically revised to meet the needs of both students and faculty. This is different than in a study conducted at the University of Iowa, which focused on EBD implementation for all four years but was separated by class requirements and classes 21 …”
Section: Discussionmentioning
confidence: 63%
“…This limitation was supported by direct faculty mentorship and expert librarians’ providing guidance to the teams for case selection, EBD search, and case presentation. It is important to mention, as noted in the Iowa study, 21 the need for faculty development while requiring direct mentorship for students in integrating EBD concepts.…”
Section: Discussionmentioning
confidence: 99%
“…Hinton et al (2015) reported successfulness of a comprehensive 4-year curriculum in EBD that had been launched in 2008 in Texas A&M University Baylor College of Dentistry 18 . Furthermore, many dental schools have integrated EBD content into dental curriculum [19][20][21][22][23] and have emphasized on EBD skills in new generation of dental students as a paramount importance for the future of dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…In 4 of the examples, measured performance improvement was shown, each with some extended effort in developing respective exercises. 3,[5][6][7] Still in the early stages, the emulation model does not reveal the student's ability to conceptualize patient situations. The difference between critical thinking skill sets that derive probing questions and those calling on the student to conceptualize may be substantial.…”
Section: Context For Critical Thinking Learning Methodologymentioning
confidence: 97%
“…Critical thinking skillsets have been developed and reported for treatment planning, literature search, and critique, caries risk assessment, technology decision-making, EBD, geriatric risk assessment, IPP, reflections/situation analysis, behavior management, case presentation. [1][2][3][4][5][6][7][8][9] These peer-reviewed skillsets can aid in showing milestones so far established for explicit learning outcomes in critical thinking and can give insights to extend the boundaries to include conceptualizing the patient interaction. Emulation models in progress will demonstrate critical thinking skillsets deriving probing questions from the expert in social work and ethics.…”
Section: Introduction and Background On Models For Critical Thinking mentioning
confidence: 99%